A bronchoalveolar lavage‐driven antimicrobial treatment improves survival in hematologic malignancy patients with detected lung infiltrates: A prospective multicenter study of the SEIFEM group. Issue 10 (9th August 2019) - Marchesi, Francesco; Cattaneo, Chiara; Criscuolo, Marianna; Delia, Mario; Dargenio, Michelina; Del Principe, Maria Ilaria; Spadea, Antonio; Fracchiolla, Nicola Stefano; Melillo, Lorella; Perruccio, Katia; Alati, Caterina; Russo, Domenico; et al.
Abstract: Bronchoalveolar lavage (BAL) is recommended for diagnosing lung infiltrates (LI) in patients with hematologic malignancy (HM). Prospective data on the impact of BAL on survival are still lacking. We conducted a prospective observational study on patients who performed BAL for LI among 3055 HM patients hospitalized from January to September 2018. The BAL was performed in 145 out of 434 patients who developed LI, at a median time of four days from LI detection. The median age was 60 (1‐83). Most patients had an acute myeloid leukemia/myelodisplastic syndrome (81), followed by lymphoma (41), acute lymphoblastic leukemia (27), and other types of HM (36). A putative causal agent was detected in 111 cases (76%), and in 89 cases (61%) the BAL results provided guidance to antimicrobial treatment. We observed a significantly improved outcome of LI at day +30 in patients who could receive a BAL‐driven antimicrobial treatment (improvement/resolution rate: 71% vs 55%; P = .04). Moreover, we observed a significantly improved outcome in 120‐day overall survival (120d‐OS) (78% vs 59%; P = .009) and 120‐day attributable mortality (120d‐AM) (11% vs 30%; P = 0.003) for patients who could receive a BAL‐driven treatment. The multivariate analysis showed that BAL‐driven antimicrobial treatment was significantly associated with better 120d‐OS and lower 120d‐AM. We did not observe any severe adverse events. In conclusion BAL allows detection of a putative agent of LI in about 75% of cases, it is feasible and well tolerated in most cases, demonstrating that a BAL‐driven antimicrobial treatment allows improvement of clinical outcome and survival.